GAMIFICATION OF ANATOMY TEACHING: strategies for remote study of anatomy - Beatriz Elaine Lima Sousa; Thiago Machado da Silva Acioly; Diego Carvalho Viana (Revista Eletrônica Científica Ensino Interdisciplinar, 2022)
The teaching and learning of Animal Anatomy is always very challenging for both the teacher and the student, a challenge that has been increased immensely with the emergence of the new coronavirus, almost completely changing the way of teaching, reflecting in new methodologies of active learning. With this, the present work aims to report the experience and results of such methodologies applied to the remote teaching of Animal Anatomy in the context of higher education, 2020, second semester, at the Universidade Estadual da Região Tocantina do Maranhão (UEMASUL), Brazil. In a class of 40 students aged between 19 and 35 years old, a division into six groups, which was determined to have developed a digital material in the format of a didactic game of their choice and that would present among the contents studied.